2017
DOI: 10.1039/c7ra07815c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculation and experiment study on the electronic structure, microstructures and photocatalytic activity of N–Al codoped TiO2

Abstract: To more accurately demonstrate how the electronic structure was changed and to explain the origin of the enhanced photocatalytic activity by N–Al codoped TiO2, we investigated N, Al monodoped, and codoped TiO2 by theoretical calculation and experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The large E g makes its photo-responsive only to the ultraviolet light (about 5% of the total solar spectrum), great limiting the light utilization rate. Tremendous experimental and theoretical research has demonstrated that, ion doping is an effective way to raise the photocatalytic performance of TiO 2 by lowering its E g and/or reducing the recombination rate of photogenerated electron-hole pairs [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The large E g makes its photo-responsive only to the ultraviolet light (about 5% of the total solar spectrum), great limiting the light utilization rate. Tremendous experimental and theoretical research has demonstrated that, ion doping is an effective way to raise the photocatalytic performance of TiO 2 by lowering its E g and/or reducing the recombination rate of photogenerated electron-hole pairs [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%